Rola marki na rynkach zagranicznych - Skulski, Przemysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
One of the globalization's effects is the increasing role of the branding on international markets. This element is visible especially in marketing activity of global companies. However, the term branding is connected not only with goods and services. The role of so-called export branding and country branding is also increasing. One of the most interesting theories is "Brand New Justice" created by Simon Anholt. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 320-328